Ideas and ideals in Jørn Utzon's courtyard houses: dwelling, nature, and Chinese architecture. Issue 5 (3rd July 2020) - Chiu, Chen-Yu; Goad, Philip; Myers, Peter; Yılgın, Cem
Abstract : The international recognition of Jørn Utzon's professional career is accompanied by a growing interest in the Danish architect's courtyard housing projects. But previous scholarship had access to limited material from Utzon's professional career, compared to what is now available in The Utzon Archives . Based on a detailed study of presently accessible archival material and original interviews with Utzon's family and affiliates, this article shows that the Danish architect's courtyard housing projects closely reflected both his architectural philosophy in general and his thoughts on modern dwellings in particular. These were in turn cultivated by the ideas and ideals of Lin Yutang, Alvar Aalto, and Osvald Sirén.